Optimization of the phenylurea moiety in a phosphoinositide 3-kinase (PI3K) inhibitor to improve water solubility and the PK profile by introducing a solubilizing group and ortho substituents. Issue 13 (1st July 2016) - Kawada, Hatsuo; Ebiike, Hirosato; Tsukazaki, Masao; Yamamoto, Shun; Koyama, Kohei; Nakamura, Mitsuaki; Morikami, Kenji; Yoshinari, Kiyoshi; Yoshida, Miyuki; Ogawa, Kotaro; Shimma, Nobuo; Tsukuda, Takuo; et al.
Graphical abstract: Abstract: Phosphoinositide 3-kinase (PI3K) is a promising anti-cancer target, because various mutations and amplifications are observed in human tumors isolated from cancer patients. Our dihydropyrrolopyrimidine derivative with a phenylurea moiety showed strong PI3K enzyme inhibitory activity, but its pharmacokinetic property was poor because of lack of solubility. Herein, we report how we improved the solubility of our PI3K inhibitors by introducing a solubilizing group and ortho substituents to break molecular planarity.